Akuntansi Sosial Spiritual Antara “Innaa Lillaahi wa Innaa Ilaihi Raaji’uun” dan “lakum Diinukum wa Liya Diin” - Nur Muchamad Kurniawan; Sri Mulyati (Jurnal Akuntansi dan Keuangan Islam, 2018)
This study aims to explain socio-spiritual accounting from the point of view of entity theory and shariah enterprise theory and to analyze the difference between both. The indicator of analysis in this study is the three dimensions offered by Global Reporting Initiative (GRI) with several combinations offered by Islamic Social Reporting (ISR): economic, social and environmental dimension with additional spiritual dimension. The main source in this research is referenced through literature study from scientific journals and books. The results show that if entity theory is reflected for social activities, it will be tendence to emphasize the need of shareholders and only report for pseudo sustainability reports. While shariah enterprise theory that is reflected for social activities will complement the enterprise theory and will account for it vertically and horizontally and will report for humanism sustainability report. GRI that is created on the basic of human ethics and reason seems to be paired with the ISR, so that tauhid values can be realized by each party either themselves, individuals or entities